2022
DOI: 10.1007/s13353-022-00697-w
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study relating genotype profiles with race performance in racing pigeons

Abstract: This is a prospective study to investigate the impact of genotype profiles on race performance in racing pigeons. Genotypes studied included lactate dehydrogenase A (LDHA), dopamine receptor (DRD), myostatin (MSTN), and feather keratin (F-KER), as well as demographic factors such as gender, color, and the mtDNA. This study shows differences within genotypes DRD456 (P = 0.027) and F-KER (P = 0.018). For DRD456, race coefficients were lower (= better performance) for genotype CT. For F-KER, race coefficients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…While there are limitations with a retrospective analysis of genotype relating to race performance, in our report such analysis was used to test the hypothesis generated from our large prospective study [7]. It is very encouraging to see that our results indicate that pigeons in our family of birds with the genotype DRD4 CCCT and F-KER TT seem to be very likely consistent Top10% race performers over all distances including the final longest distance of around 325-400 miles.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…While there are limitations with a retrospective analysis of genotype relating to race performance, in our report such analysis was used to test the hypothesis generated from our large prospective study [7]. It is very encouraging to see that our results indicate that pigeons in our family of birds with the genotype DRD4 CCCT and F-KER TT seem to be very likely consistent Top10% race performers over all distances including the final longest distance of around 325-400 miles.…”
Section: Discussionmentioning
confidence: 70%
“…In the quest to identify genotypes relating to race performance in racing pigeons multiple studies reported about the effect of variability in a single gene [1][2][3][4][5][6][7][8][9][10][11][12]. Most frequently reported genes are LDHA, DRD4, F-KER, and more recently CRY1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that mRNA expression of MSTN is significantly higher in breast muscle than in other tissues and increases with at 1-28 days (Liu et al, The MSTN gene exon 3 c.C861T (p.T287T) synonymous mutation has been observed in the meat, carrier and ornamental pigeon populations (Dybus et al, 2013). The T allele frequency is higher in the meat pigeon population, and statistical correlation between the mutation and competition ability cannot be obtained in the carrier pigeon population owing to the low gene frequency of mutant TT (Dybus et al, 2018;Kolvenbag et al, 2022). However, there is a lack of correlation validation between MSTN p.T287T and MM phenotype data.…”
Section: Discussionmentioning
confidence: 99%
“…In pigeon research, a candidate gene may be proposed, and, using homing and non-homing pigeons ( Columba livia domestica ) and racing records, potential associations between racing performance and DNA polymorphisms can be uncovered. In the group of potential genetic markers of pigeons’ racing performance are the LDHA gene [ 30 , 31 , 32 , 33 ], DRD4 [ 34 , 35 ], FCBP ( F-KER ) [ 35 , 36 , 37 ], CRY1 [ 38 ] and MSTN [ 39 ]. In whole genome analyses of 95 pigeons of various breeds, polymorphisms in the GSR and LRP8 genes have been identified as a potential markers of racing performance in homing pigeons [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%